Korelasi persentase lemak tubuh dengan kadar adipsin pada premenopause - Rahmani Welan; Gusti Revilla; Desmawati Desmawati (Jurnal Gizi Klinik Indonesia, 2018)
Background: One of the conditions on premenopausal period is the increase in body fat, among which are caused by levels of the fluctuating estrogen hormone. Increase fat affects the body fat percentage and adipsin levels. Adipsin plays a role in the stimulation of insulin secretion by producing C3a, in which C3AR1 (C3a Receptor 1) fragments interact with beta cells to secrete insulin.Objective: The purpose of this study is to determine correlation of body fat percentage with adipsin levels on premenopause.Design: This was an analytical study with cross-sectional design. Body fat percentage was obtained by examination using Bioelectrical Impedance Analysis (BIA). Venous blood was taken at the mediana cubiti area used for serum adipsin levels. Adipsin levels were analyzed by Enzyme-linked Immunosorbent Assay (ELISA) technique.Results: The mean of body fat percentage on premenopausal was 36,18 ± 8,35%. The mean of adipsin levels on premenopausal was 117,05 ± 87,93 ng/ml. Result of Pearson test analysis got value r = 0,632 and value p = 0.0005 (p <0,05).Conclusions: There is a positive significant correlation between the percentage of body fat with adipsin levels on premenopause.